2013
DOI: 10.1002/cyto.a.22276
|View full text |Cite
|
Sign up to set email alerts
|

R‐phycoerythrin‐conjugated antibodies are inappropriate for intracellular staining of murine plasma cells

Abstract: Phycoerythrin (PE) is a type of phycobiliproteins found in cyanobacteria and red algae. PE-conjugated antibodies are broadly used for flow cytometry and immunofluorescence microscopy. Because nonspecific binding of antibodies results in decreased analytic accuracy, numerous efforts have been made to unveil cases and mechanisms of nonspecific bindings. However, nonspecific binding of specific cell types by a fluorescent dye-conjugated form of antibody has been rarely reported. In the present study, we discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…While it has been reported that ASCs non-specifically retain PE in the context of ICFC (Bohacova et al, 2021;Kim and Kim, 2013), our current study confirms and extends these findings to include PE/Cy7. A key finding shown here is that the mere act of repetitive centrifugation post-fixation appears to induce the ASC retention of PE.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…While it has been reported that ASCs non-specifically retain PE in the context of ICFC (Bohacova et al, 2021;Kim and Kim, 2013), our current study confirms and extends these findings to include PE/Cy7. A key finding shown here is that the mere act of repetitive centrifugation post-fixation appears to induce the ASC retention of PE.…”
Section: Discussionsupporting
confidence: 88%
“…PFA) and permeabilization (i.e. Sap) techniques, it has been reported that ASCs non-specifically retain PE-conjugated Abs thus making them unsuitable for ICFC (Kim and Kim, 2013). This was shown to be the case for ex vivo stained ASCs as well as those generated in vitro following B lymphocyte stimulation (Kim and Kim, 2013).…”
Section: Antibody-secreting Cells Preferentially Retain Phycoerythrin-conjugated Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…R -PE is commonly used as a fluorescent label probe [ 6 , 7 , 8 , 9 ], as biological and clinical assays [ 10 ] and for in-flow cytometry [ 8 , 11 ]. It is also used as a pigment or natural food dye [ 12 ].…”
Section: Introductionmentioning
confidence: 99%